Age-Related Changes in Listening Effort for Children and Teenagers With Normal Hearing and Cochlear Implants. Issue 3 (May 2021) - Hsu, Benson Cheng-Lin; Vanpoucke, Filiep; Langereis, Margreet; Dierckx, Ann; van Wieringen, Astrid
Abstract : Objectives: A clinically viable measure of listening effort is crucial in safeguarding the educational success of hard-of-hearing students enrolled in mainstream schools. To this end, a novel behavioral paradigm of listening effort targeting school-age children has been designed and reported in Hsu et al. (2017) . The current article consists of two follow-up experiments investigating the effects of noise, processing depth, and age in a similar paradigm, first in a group of participants with normal hearing (NH) followed by a sample of school-age cochlear implant (CI) users. Research objectives include the construction of normative values of listening effort and comparing outcomes between age-matched NH and CI participants. Design: In Experiment 1, the listening effort dual-task paradigm was evaluated in a group of 90 NH participants with roughly even age distribution between 6 and 26 years. The primary task asked a participant to verbally repeat each of the target words presented in either quiet or noise, while the secondary task consisted of categorization true-or-false questions "animal" and "dangerous, " representing two levels of semantic processing depth. Two outcome measures were obtained for each condition: a classic word recognition score (WRS) and an average response time (RT) measured during the secondary task. The RT was defined as the main listening effort metric throughout the study. Each NH participant's long-term memory retrieval speed and working memory capacity were also assessed through standardized tests. It was hypothesized that adding noise would negatively affect both WRS and RT, whereas an increase in age would see significant improvement in both measures. A subsequent Experiment 2 administered a shortened version of the paradigm to 14 school-age CI users between 5 and 14 years old at a university clinic. The patterns of results from the CI group were expected to approximate those of the NH group, except with larger between-subject variability. Results: For NH participants, while WRS was significantly affected by age and noise levels, RT was significantly affected by age, noise levels, and depth of processing. RT was significantly correlated with long-term memory retrieval speed but not with working memory capacity. There was also a significant interaction effect between age and noise levels for both WRS and RT. The RT data set from the NH group served as a basis to establish age-dependent 95% prediction intervals for expected future observations. For CI participants, the effect of age on the two outcome measures was more visible when target words were presented in quiet. Depending on the condition, between 35.7% and 72.7% of the children with CI exhibited higher-than-norms listening effort as measured by categorization processing times. Conclusion: Listening effort appears to decrease with age from early school-age years to late teenage years. The effects of background noise and processing depth are comparable with those reported in Hsu et al. (2017) . Future studies interested in expanding the paradigm's clinical viability should focus on the reduction of testing time while maintaining or increasing the sensitivity and external validity of its outcome measures.